2022
DOI: 10.3390/molecules28010303
|View full text |Cite
|
Sign up to set email alerts
|

Triterpenic Acid Amides as Potential Inhibitors of the SARS-CoV-2 Main Protease

Abstract: Although the incidence and mortality of SARS-CoV-2 infection has been declining during the pandemic, the problem related to designing novel antiviral drugs that could effectively resist viruses in the future remains relevant. As part of our continued search for chemical compounds that are capable of exerting an antiviral effect against the SARS-CoV-2 virus, we studied the ability of triterpenic acid amides to inhibit the SARS-CoV-2 main protease. Molecular modeling suggested that the compounds are able to bind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…The results obtained are consistent with the results published earlier (Jin et al, 2020), (Lockbaum et al, 2021;Zakharova et al, 2021) (Figure 4), which confirms that 3SL retains its properties when expressed in E. coli cells. The use of this test system makes it possible both to detect new inhibitors of the main viral protease (Baev et al, 2022) and to study the mechanism of action of compounds that have shown activity against the infectious SARS-CoV-2 virus (Filimonov et al, 2022).…”
Section: Authenticity Analysis Of the 3cl Proteasementioning
confidence: 99%
“…The results obtained are consistent with the results published earlier (Jin et al, 2020), (Lockbaum et al, 2021;Zakharova et al, 2021) (Figure 4), which confirms that 3SL retains its properties when expressed in E. coli cells. The use of this test system makes it possible both to detect new inhibitors of the main viral protease (Baev et al, 2022) and to study the mechanism of action of compounds that have shown activity against the infectious SARS-CoV-2 virus (Filimonov et al, 2022).…”
Section: Authenticity Analysis Of the 3cl Proteasementioning
confidence: 99%
“…One of the encouraging fields of medicinal chemistry for the synthesis of new agents with antiviral activity is the use of natural compounds as a starting platform, which has recently received special attention [ 17 , 18 , 19 , 20 ]. We have earlier identified effective borneol-based inhibitors of entry of a wide range of SARS-CoV-2 viruses using a pseudoviral system [ 21 ], using a surrogate system of triterpene acid–based amides as inhibitors of the main viral protease [ 22 ]. Glycyrrhizic acid nicotinates have also been shown to be inhibitors of SARS-CoV-2 viruses [ 23 ].…”
Section: Introductionmentioning
confidence: 99%